A snoRNA modulates mRNA 3′ end processing and regulates the expression of a subset of mRNAs. Issue 15 (26th July 2017) - Huang, Chunliu; Shi, Junjie; Guo, Yibin; Huang, Weijun; Huang, Shanshan; Ming, Siqi; Wu, Xingui; Zhang, Rui; Ding, Junjun; Zhao, Wei; Jia, Jie; Huang, Xi; et al.
Abstract: mRNA 3′ end processing is an essential step in gene expression. It is well established that canonical eukaryotic pre-mRNA 3′ processing is carried out within a macromolecular machinery consisting of dozens of trans-acting proteins. However, it is unknown whether RNAs play any role in this process. Unexpectedly, we found that a subset of small nucleolar RNAs (snoRNAs) are associated with the mammalian mRNA 3′ processing complex. These snoRNAs primarily interact with Fip1, a component of cleavage and polyadenylation specificity factor (CPSF). We have functionally characterized one of these snoRNAs and our results demonstrated that the U/A-rich SNORD50A inhibits mRNA 3′ processing by blocking the Fip1-poly(A) site (PAS) interaction. Consistently, SNORD50A depletion altered the Fip1–RNA interaction landscape and changed the alternative polyadenylation (APA) profiles and/or transcript levels of a subset of genes. Taken together, our data revealed a novel function for snoRNAs and provided the first evidence that non-coding RNAs may play an important role in regulating mRNA 3′ processing.